The Witches - Dahl, Roald; Illustrated by Blake, Quentin (London Puffin Books, 2013)
A young boy and his Norwegian grandmother, who is an expert on witches, together foil a witches' plot to destroy the world's children by turning them into mice.
Include Illustrations
Keywords: Children's stories, English